Understanding Gold Investment Trends Among Working Women in Haryana: Awareness and Influencing Factors (International Journal of Environmental Sciences, 2025)
This study examines the gold investment trends among working women in Haryana, emphasizing their awareness, preferences, and the factors influencing their investment decisions. The dual cultural and financial significance of gold in Indian society, alongside the rising prominence of modern investment avenues like digital gold and ETFs, is explored.A descriptive research design was utilized, with data collected from 360 respondents across six divisions of Haryana using structured questionnaires. Quantitative and qualitative methods, including factor analysis, were applied to evaluate the factors shaping investment behaviors and preferences.The findings reveal that traditional gold remains the most preferred investment option due to its cultural importance, with 78% of respondents favoring it. However, awareness of modern alternatives such as digital gold and ETFs is limited, with only 45% reporting familiarity. Key influences include cultural attachment, financial stability, and liquidity. Factors like financial literacy and access to diversified investment tools emerged as critical in shaping decisions.This research highlights the unique intersection of tradition and modernity in gold investments among working women in a non-metropolitan region. It emphasizes the need for tailored financial literacy initiatives and innovative investment options to empower women, ensuring a balance between traditional values and financial independence.